Islamic Religious Education Teachers’ Strategies in Cultivating Spiritual Literacy among Students - Muhhi, Oon Mukron Abdul (LifeSciFi, 2026)
This study is motivated by the critical role of strengthening students’ spiritual literacy as a core objective of Islamic education. Islamic education teachers play a central role in nurturing religious habits, modelling spiritual behavior, and implementing reflective and contextual learning strategies. To analyze how religious habituation, Islamic education teacher exemplarity, and reflection-based learning strategies collectively contribute to strengthening students’ spiritual literacy. Employing a qualitative descriptive method, the research collects data through observations of school religious activities, interviews with teachers and students, and documentation of school religious programs. The findings reveal that strategies such as daily Qur’an recitation (tadarus), collective prayers, congregational Dhuha prayers, and Qur’anic literacy programs effectively enhance students’ discipline in worship and spiritual awareness. Teacher exemplarity and active student participation further reinforce the internalization of religious values, while reflective and humanistic learning approaches enable students to cognitively understand, internalize, and apply these teachings in daily life. The study concludes that religious habituation, teacher role modelling, and reflective learning are essential in strengthening spiritual literacy, emphasizing the need for institutional support and innovative, sustainable Islamic education programs.